The effect of entrepreneurial characteristics and competitive advantage on entrepreneurial success moderated by emotional intelligence (case study on processed food and grocery smes in semarang city) - Ari Pranaditya; Kharis Raharjo (Institute of Computer Science (IOCS), 2022)
The multidimensional crisis hit Indonesia as a result of the prolonged outbreak of the Covid-19 pandemic virus since 202.1 which has not ended until now. The negative impact will paralyze the business world, destabilize the foundations of the welfare of the wider community, the world of work is getting narrower, while people who need work continue to increase, unemployment continues to increase. The phenomenon of these problems, as the right solution is to develop an entrepreneurial spirit. This research aims to analyze the variables that affect the success of entrepreneurship. Some of the variables that are thought to be able to influence it are; Characteristics of Entrepreneurship, Competitive Advantage and Emotional Intelligence as Moderating Variables. The population in this study is MSME Processed Food and Grocery in Semarang City. The sample in this study used a non-probability sampling method with purposive sampling technique, obtained a sample of 304 (10 x 30) + 4. The variables consisted of four variables; Characteristics of Entrepreneurship, Competitive Advantage (As Independent Variables), and Emotional Intelligence (As Moderating Variables), while Entrepreneurial Success (As Dependent Variables). The method of data analysis was done by testing the hypothesis (t-test), and testing the moderating variable using MRA (Moderated Regression Analysis).